The Prehistoric and Early Use of Pitchstone and Obsidian: With Report on Petrology; and a Note of Egyptian and Aegean Discoveries - Mann, Ludovic McLellan; Scott, A; Petrie, W M Flinders (Proceedings of the Society of Antiquaries of Scotland, 1918)
The volcanic glass of Scotland and Ireland is called pitchstone, and the often more solid and homogeneous natural glass found in foreign places is known as obsidian. The pitchstone of Ireland and of Scotland, except that of the Island of Arran, is apparently too much cracked into small pieces to be of use. Pitchstone is rare in Scotland, and the Island of Arran possesses most of the outcrops. Pitchstone when splintered presents razor-like edges nearly as useful as those on flint flakes for scraping, cutting, boring, and piercing. It is more brittle than flint, and does not allow of the same delicate secondary workmanship as, for example, is entailed in the cutting out of barbs on arrowheads. No worked pitchstone seems to have been recorded from Britain outside of Arran, Bute, Ayrshire, and Wigtownshire, and the only source of supply of the raw material seems to have been Arran. No prehistoric British or Irish pitchstone drippings or anciently-worked pieces are apparently to be found in English or Irish collections. There is no clear evidence as to pitchstone chippings or implements having yet been discovered in Ireland. The use of pitchstone spans the Neolithic and Bronze Age with sporadic early Iron Age examples in Scotland. The Greek island of Melos has abundant sources of obsidian while pre-dynastic artefacts are known from Egypt.